PENGARUH KOMUNIKASI DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PT Z - Della Restu Cahyani; Dian Sudiantini; Bintang Narpati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the influence of communication and teamwork on employee performance of PT Zr. This type of research is quantitative. The sampling technique used is saturated sampling, where the number of population and samples is 50 respondents. Data collection using a questionnaire that had been tested for validity and reliability. Data processing using Statistical Program For Social Science (SPSS) version 27. Data analysis techniques are carried out using multiple linear regression analysis. And the results of this study indicate that: (1) The communication has a positive and significant effect on employee performance. (2) The teamwork has a positive and significant effect on employee performance. (3) The communication and teamwork have a positive and significant effect on employee performance.